Functional relevance of genes predicted to be affected by epigenetic alterations in atypical teratoid/rhabdoid tumors - Tegeder, Isabel; Erkek, Serap; Johann, Pascal-David; Thatikonda, Venu; Kool, Marcel (Journal of neuro-oncology, 2019)
PurposeAtypical teratoid/rhabdoid tumor (ATRT) is a highly malignant brain tumor predominantly arising in infants. Mutations of SWI/SNF chromatin remodeling complex members SMARCB1/INI1 or (rarely) SMARCA4/Brg1 are the sole recurrent genetic lesions. Epigenetic studies revealed a large number of genes predicted to be affected by differential histone modifications in ATRT, but the role of these genes in the biology of ATRT remains uncertain. We therefore aimed at exploring the role of these genes in the detrimental effects of SMARCB1-deficiency.MethodsThe functional relevance of 1083 genes predicted to be affected by epigenetic alterations in ATRT was examined in vivo using a Drosophila melanogaster model of SMARCB1-deficiency. Human orthologues of genes whose knockdown modified the phenotype in the Gal4-UAS fly model were further examined in ATRT samples and SMARCB1-deficient rhabdoid tumor cells.ResultsKnockdown of Snr1, the fly orthologue of SMARCB1, resulted in a lethal phenotype and epigenetic alterations in the fly model. The lethal phenotype was shifted to later stages of development upon additional siRNA knockdown of 89 of 1083 genes screened in vivo. These included TGF-beta receptor signaling pathway related genes, e.g. CG10348, the fly orthologue of transcriptional regulator PRDM16. Subsequently, PRDM16 was found to be over-expressed in ATRT samples and knockdown of PRDM16 in SMARCB1-deficient rhabdoid tumor cells reduced proliferation.ConclusionsThese results suggest that a subset of genes affected by differential histone modification in ATRT is involved in the detrimental effects of SMARCB1-deficiency and also relevant in the biology of ATRT.
First Online: 16 November 2018
Gesehen am 09.05.2019